Information Fusion and Geographic Information Systems Proceedings of the Third International Workshop - Popovich, Vasily V.; Schrenk, Manfred; Korolenko, Kyrill V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This volume contains the papers presented at the International Workshop (3z(BInf- mation Fusion and Geographical Information Systems(3y (B(IF&GIS$1 (B07) held in St. Petersburg, Russia, during May 27-29, 2007. The workshop was organized by the St. Petersburg Institute for Informatics and Automation of the Russian Academy of Sciences (SPIIRAS). Research in the Geosciences field interprets the concept of Information Fusion as a synonym of an approach that permits research into all the problems and issues which program-makers and scientific researchers are faced with. Thus, topics that are to be covered during the workshop relate to issues such as harmonization, - tegration and information fusion. At the same time the spectrum of problems - der discussion exceeds the current bounds of developing GIS applications. This is a significant modern trend since GIS technology is more often used as an interface in support and decision making systems. As a result, it is difficult to consider Geoinformation Science without considering related scientific directions such as Ontology, Artificial Intelligent Systems and Situation Management.s
Invited Papers -- New Challenges for Defining Information Fusion Requirements -- Situation Management: Basic Concepts and Approaches -- Maritime GIS: From Monitoring to Simulation Systems -- Data, Information and Knowledge Harmonization, Integration and Fusion in GIS -- Intelligent Images Analysis in GIS -- Context-Driven Information Fusion for Operational Decision Making in Humanitarian Logistics -- From Battle Management Language (BML) to Automatic Information Fusion -- Centrope MAP: Combining X-Border Information from Multiple Sources for Planning Purposes -- Information Assurance and Protection in GIS -- Software Environment for Simulation and Evaluation of a Security Operation Center -- Security Policy Verification Tool for Geographical Information Systems -- Architecture Types of the Bit Permutation Instruction for General Purpose Processors -- New Public Key Cryptosystems Based on Difficulty of Factorization and Discrete Logarithm Problems -- GIS as a Basis for Monitoring Systems -- Application of a Dynamic Recurrent Neural Network in Spatio-Temporal Forecasting -- System of Traffic Control on the Basis of Cartographic Databases and Geoinformation Technologies -- Information Fusion of Land Laser Scanning for Geographic Information Systems -- Using GIS to Analyze Acute Myocardial Infarction in Turkey -- Ontologies and Programming Technologies for GIS and GIS Applications -- Obtaining Semantic Descriptions Based on Conceptual Schemas Embedded into a Geographic Context -- Representing the Semantic Content of Topological Relations into Spatial Databases -- Some Remarks on Topological Abstraction in Multi Representation Databases -- Intelligent Simulation of Hydrophysical Fields by Immunocomputing -- Visual Modeling of Spatial Processes -- Universal Data Model for Intelligent GIS -- 3D Graphics Applied to Maritime Safety -- Operations Research and TSMO for GIS Applications -- Northern Shield US-Russia Maritime Energy Security Cooperation -- Space-Extensive Targets Radar Search in the Presence of Noise -- Empirical Bayes Trajectory Estimation Based on Bearings from Moving Observer.
Keywords: Geography; Computer simulation; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Simulation and Modeling; Environmental Monitoring/Analysis.; Electronic books